MSME Product Innovation as a Competitiveness Strategy in Local and Global Markets - Mufid Andrianata; Sudarmiatin Sudarmiatin; Wening Patmi Rahayu (Oikonomia : Journal of Management Economics and Accounting, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in the Indonesian economy with significant contributions to Gross Domestic Product (GDP) and employment. However, in facing the challenges of globalization and increasingly fierce competition, MSMEs are required to innovate to remain relevant and competitive. Innovation is key to improving product competitiveness by adopting digital technology, integrating traditional elements with modern designs, and utilizing e-commerce platforms and social media. Trend phenomena such as increasing interest in local products with a modern touch, environmentally friendly designs, and unique narratives in marketing are increasingly encouraging MSMEs to adapt quickly. This research uses a descriptive qualitative approach to understand the innovation strategies of MSMEs in Yogyakarta, involving interviews, observation, and documentation. The results show that MSMEs that are able to combine traditional elements with modern innovations can expand their markets internationally. Collaboration with external parties such as startups and business incubators also plays an important role in enriching product quality and expanding market reach. Thus, continuous innovation and support from various parties are the main drivers for MSMEs to continue to grow in a competitive global market